Growth, structure, and spectroscopic properties of a Cr3+, Tm3+, Ho3+, and Pr3+ co-doped LuYAG single crystal for 2.9 μm laser. Issue 31 (6th July 2016) - Zhang, Huili; Sun, Dunlu; Luo, Jianqiao; Peng, Fang; Fang, Zhongqing; Zhao, Xuyao; Cheng, Maojie; Zhang, Qingli; Guo, Qiang; Yin, Shaotang
Abstract : The new Cr, Tm, Ho, Pr:LuYAG is a promising crystal to realize 2.911 μm laser pumped by a flash lamp or 783 nm LD. Abstract : A new laser crystal from Lu2.4 Y0.6 Al5 O12 (LuYAG) co-doped with Cr 3+, Tm 3+, Ho 3+, and Pr 3+ ions was grown successfully by the Czochralski method for the first time. The structure parameters of the Cr, Tm, Ho, Pr:LuYAG crystal are determined by the X-ray Rietveld refinement method. The main absorption bands are observed near 426 and 782 nm, and the fluorescence spectrum excited by a 450 nm or 783 nm LD presents an emission band near 2.911 μm, indicating that the co-doped Cr 3+ and Tm 3+ ions can be utilized as sensitizers for the Ho 3+ ions. The lifetimes of the 5 I6 and 5 I7 levels of the Ho 3+ ions were measured and fitted to be 0.070 ms and 1.852 ms, respectively. The energy transfer efficiencies of the processes 5 I6 (Ho 3+ ) → 3 F3, 4 (Pr 3+ ) and 5 I7 (Ho 3+ ) → 3 F2 (Pr 3+ ) + 3 H6 (Pr 3+ ) were calculated, showing that the Pr 3+ ions can play the role of a deactivator for the Ho 3+ ions. Furthermore, the energy transfer mechanisms among the Cr 3+, Tm 3+, Ho 3+, and Pr 3+ ions were studied. The results suggest that the Cr, Tm, Ho, Pr:LuYAG crystal is a new promising laser medium operating at around 2.9 μm under flash lamp or 783 nm LD pumping.